Digital Photography Interactive Multimedia (DPIM) / Liyana Puasa - Puasa, Liyana (2007)
Photography is becoming popular with the introduction of digital cameras. However, a courseware which teaches digital photography is hard to come by, moreover, one that is offered in Malay language. The Digital Photography Interactive Multimedia (DPIM) courseware intends to fill this void. DPIM was developed using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) methodology. Its learning model is based on Experiential Learning by Carl Rogers. The main engine of DPIM is Macromedia Flash MX v8.0. DPIM consist of five main modules which are the Digital Camera, Basic Techniques, Advanced Techniques, Tests and Help